THE THERMOELECTRLC POWER OF THE MAGNETLC Fe-Mn-Al COMPOUNDS - Al-Ani, Silwan Kamal (Iraqi Journal of Physics, 2002)
The thermoelectric power as a function of temperature for the Iron-Manganese-Aluminum, Fe-Mn-Al, alloys for manganese concentrations 0.04, 0.06, 0.08, 0.10 and 0.20 have been investigated in the temperature range 300 K. to 500 K. these results showed that the thermoelectric power coefficient in hot probe measurements showed that the electrons are the majority charge carriers in these alloys.